The Effect of Workload and Employee Turnover on Employee Performance at PT. Wijaya Karya Beton Deli Serdang Branch Office (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Wijaya Karya Beton Deli Serdang Branch Office is a company in the precast concrete industry. The phenomenon in the company is that employee performance is declining because the workload received by employees is too heavy and employee turnover is quite high. This study uses a quantitative descriptive research type. The population in the study was 93 employees with a sampling technique using saturated samples so that 93 samples were obtained. Simultaneously, there is a significant influence between the variables of workload and employee turnover on the performance of employees of PT. Wijaya Karya Beton Deli Serdang Branch Office. While partially, it was found that the workload variable did not have a significant effect on the performance of employees of PT. Wijaya Karya Beton Deli Serdang Branch Office. Partially, it was found that the employee turnover variable did not have a significant effect on the performance of employees of PT. Wijaya Karya Beton Deli Serdang Branch Office.